An epidemiological evaluation of the Clinical Risk Index for Babies (CRIB) at the Tygerberg neonatal intensive care unit - Pieper, Clarissa Hildegard (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.